Association between delivery of small-for-gestational-age neonate and long-term maternal chronic kidney disease. (1st September 2016) - Almasi, Ofir; Pariente, Gali; Kessous, Roy; Sergienko, Ruslan; Sheiner, Eyal
Abstract: Objective : To investigate whether delivery of a small for gestational age (SGA) neonate poses a risk for subsequent long-term maternal renal disease. Study design : A population-based study was conducted. Comparison was performed regarding the incidence of long-term renal morbidity in a cohort of women with and without a previous delivery of a SGA neonate. Deliveries occurred during a 25-year period, with a mean follow-up duration of 11.2 years. Renal morbidity included kidney transplantation, chronic renal failure and hypertensive renal disease. Cox proportional hazards model was used to estimate the adjusted hazards ratio (HR) for renal-related hospitalizations and mortality. Results : Out of 99 342 deliveries that met the inclusion criteria, 10 701 (10.7%) occurred in patients who had at least one previous delivery of a SGA neonate. During the follow-up period, patients with a delivery of an SGA neonate had higher rates of renal-related hospitalizations (0.2% versus 0.1%; OR = 1.6, 95% CI 1.01–2.5; p = 0.04). In a Cox proportional hazards model, adjusted for confounders, previous delivery of a SGA neonate was independently associated with subsequent maternal renal-related hospitalizations (adjusted HR, 1.7; 95% CI 1.1–2.8). Conclusion : Delivery of a SGA neonate is an independent risk factor for long-term maternal renal disease.